Review on Different Beneficial Ways of Applying Alum Sludge in a Sustainable Disposal Manner - Odimegwu, Temple Chimuanya; Zakaria, I.; Abood, M. M.; Nketsiah, C. B. K.; Ahmad, M. (Salehan Institute of Higher Education, 2018)
Disposal of waste from water treatment plant is one of the major issues most treatment plants seem not to overcome due to the constant generation of this waste as a result of meeting the demand of water and purification of water for human consumption. The effect of disposing sludge constantly in the environment has called for an economical and sustainable way of reusing alum sludge. However, this paper aimed at reviewing the possible literature on applying waste from water treatment plant in various ways, example; in building material; as brick and tiles, in concrete ; as replacement of cement and aggregate, in Geotechnics; as soil stabilizer and in agriculture; as soil fertilizer, in pottery; use as replacement of clay in flower pot production for sustainable disposal. All the above mentioned categories of uses have reviled an effective and efficient way in managing waste from water treatment plant (alum sludge), also a safer and economical manner of disposal.Â However, the effects when used and the behaviour when it is incorporated with other materials were highlighted, other reuse and disposal options where discussed and the areas not covered (knowledge gap) was identified.